Seasonal variation in egg nutrient composition under a pasture-based layer hen system: Implications for sustainable agriculture - Rachel Van Duinen; Selin Sergin; Shreya Chavva; Julianna K. Adams; Chad A. Bitler; Jenifer I. Fenton (PLoS ONE, 2025)
Sustainability in poultry production emphasizes systems that promote environmental health, animal welfare, and the potential to produce a more nutrient dense product. Pasture based poultry systems align with these sustainability goals by supporting soil fertility, biodiversity, and more natural behaviors. Access to pasture allows chickens to consume a diverse range of plants and insects, potentially enhancing the nutritional value of their eggs. However, environmental variability across the grazing season may influence egg nutrient profiles, impacting both nutritional quality and system resilience. This study evaluated how seasonal changes in forage quality, soil composition, and climate affect the nutrient profile of eggs produced under a regenerative, pasture-based system in Southern Ohio. Monthly collections of forage (n = 3) and eggs (n = 24, pooled into 12 replicates) occurred from May to December. Fatty acid composition was assessed using gas chromatography-mass spectrometry, while carotenoid and phenolic levels were measured colorimetrically. Vitamin and mineral content were analyzed through liquid chromatography and Inductively Coupled Plasma Optical Emission Spectroscopy. Pasture quality, assessed by total digestible nutrients (TDN), peaked in October. Egg protein quality met USDA “Grade AA” standards every month except August (p > 0.001). The highest yolk pigmentation score was recorded in December (9.5 ± 1.3; p < 0.001). Vitamin A levels were significantly greater in late summer (p < 0.001), while vitamin E gradually increased across the season, reaching its highest value in November (118.1 ± 24.0 µg/g fresh yolk; p < 0.001). Carotenoid concentrations were elevated in mid-summer and late autumn (p < 0.001). Total omega-3 fatty acids were significantly higher in September and October than in mid-summer and late fall, while the n-6:n-3 ratio was lowest in early summer, and fall compared to July (p < 0.001). Sparse partial least squares discriminant and random forest analyses demonstrated that eggs produced from September to November contained higher levels of vitamins A and E, greater essential omega-3 fatty acids, and a more favorable n-6:n-3 balance than eggs from other months. These findings highlight the need to account for seasonal variability in pasture-based systems and suggest targeted management practices could enhance year-round nutritional quality, supporting both consumer health and sustainable food production.